Hexadecylphosphocholine: Skin Treatment of Cutaneous leishmania - Iqbal, Javeid; Bashir, Sajid (Asian Journal of Chemistry, 2010)
Human leishmaniasis is a parasitic disease caused by trypnosomatid of the genus leishmania, transmitted by the bite of a sand fly of genus phlebotomus, a characteristic of all leishmanial infections in the intracellular parasitism of macrophages. Various species of leishmania have been identified causing the disease ranging from simple cutaneous to Visceral leishmaniasis. Hexadecylphosphocholine (HePC), a novel phospholipids derivative, was tested against leishmania major and leishmania tropica, the causative agent of Cutaneous leishmaniasis. Human volunteer were cured completely, when treated topically with an ointment comprising 15 % HePC and 12 % methyl benzethonium chloride in simple ointment base twice daily for 10 d. No parasites were detected in tissue smears or in culture from treated cutaneous lesions.